The awareness of generation ‘Y’ on green building development in Malaysia / Syarifah Nur Nazihah Syed Jamalulil, Haryati Mohd Isa and Nurul Huda Ahmad - Syarifah Nur Nazihah, Syed Jamalulil; Haryati, Mohd Isa; Nurul Huda, Ahmad (2015)
Malaysian construction industry has undergone over 50 years of rapid industrialization and became an economic engine for the country. The industry contributes 5% to Gross Development Product and employs almost 9.3% of overall workforce. However, most of the development has been reported as unsustainableand requires specific sustainable approach to the construction industry. This situation urges the government and professional bodies in Malaysia to take proactive actions in promoting sustainability concept for better environmental and social protection. Nevertheless, creating new sustainable construction concept highly depends on the knowledge and involvement of participants within this industry especially generation ‘Y’. This research aims to investigate the awareness of generation ‘Y’ on green building development in the Malaysian construction industry. In addition, this research also recommends means to improve the level of awareness on green building development among generation ‘Y’ in Malaysia. Data will be collected through questionnaire survey. The paper posits that it is essential to raise the awareness and educate generation ‘Y’ on green building development for continual improvement in the future.